Elemental cycles in the coralline alga Neogoniolithon hauckii as a recorder of temperature variability in the Mediterranean Sea - Hetzinger, Steffen; Grohganz, Madleen; Halfar, Jochen; Hathorne, Ed; Ballesteros, Enric; Kersting, Diego K. (Frontiers in Marine Science, 2023)
Coralline algae play important ecological roles throughout the photic zone of the world’s oceans. Recent studies have shown that attached-living coralline algae can contain records of past climate variability. So far, algal-based paleo-reconstructions are mainly available from mid- to high-latitudes, while in low latitude and temperate regions only few examples exist. Here, we investigate samples from the attached-living encrusting coralline algal species Neogoniolithon hauckii (Rothpletz) R.A Townsend & Huisman [= Neogoniolithon mamillosum (Hauck) Setchell & L.R. Mason, nom illeg.] from a temperate site in the Mediterranean Sea to assess its potential as an environmental recorder. The specimens were collected at different water depths (20 and 40 m) in the Columbretes Islands (Spain). Sclerochronological analysis of sectioned samples revealed seasonal growth patterns. Mg/Ca, Li/Ca, and Ba/Ca ratios were measured in the algal skeletons using laser ablation inductively coupled mass spectrometry (LA-ICP-MS) in ultra-high resolution. We report a mean vertical extension rate of 1.1 to 1.2 mm/year (based on analysis of Mg/Ca cycles in 40 m and 20 m samples), representing the first growth rate measurement for this species. In addition, subannual banding patterns were mapped, measured, and could be linked to high frequency variability in laser-analyzed Mg/Ca ratios. Elemental ratios analyzed in Neogoniolithon hauckii were compared to in situ water temperatures measured at the water depth of sample collection. Our results show significant positive relationships between algal Mg/Ca (R=0.55) as well as Li/Ca ratios (R=0.46) and in situ measured temperature data (40 m specimen). Ba/Ca ratios show no significant correlation to temperature and may be influenced by other factors. These data suggest potential of this species for climate reconstructions in warm-temperate regions as Neogoniolithon hauckii is not only widely distributed in the Mediterranean, but also one of the few species that may be used as a temperature archive for mesophotic coralligenous assemblages that are strongly affected by the recent anthropogenic temperature rise. Further calibration studies are needed to test the element-temperature relationships on samples with longer growth records and in different settings and water depths.